Retrospective study on the use of lidocaine constant rate infusions for the treatment of ileus in ruminants and camelids. (13th September 2021) - Yau, Katie; Halleran, Jennifer; Boileau, Melanie; Foster, Derek
Abstract: Limited knowledge exists regarding the use of lidocaine as a prokinetic in ruminants and camelids to treat gastrointestinal ileus. In this retrospective study, ruminant and camelid cases diagnosed with ileus and treated with a lidocaine constant rate of infusion were assessed for adverse reactions and medical outcomes. A review of medical records was performed to identify cases in which lidocaine was administered as a prokinetic. Ten cases were identified consisting of 8 cattle, 1 goat, and 1 alpaca. Nine animals improved with a lidocaine treatment. No adverse effects were reported during lidocaine administration. Nine animals were discharged, and 1 was euthanized.